Radicals and Anions of Siloles and Germoles. Issue 47 (6th July 2021) - Reinhold, Crispin R. W.; Schmidtmann, Marc; Tumanskii, Boris; Müller, Thomas
Abstract: Invited for the cover of this issue is the group of Thomas Müller at the University of Oldenburg. The image shows the calculated spin distribution of a persistent silacyclopentadienyl radical. Read the full text of the article at 10.1002/chem.202101415 . Abstract : " The ultimate inspiration for this project came from work of the group of Robert West (Madison) from 2003 describing a stable silole‐based biradical. It was tempting for us to explore the possibilities to prepare such neutral radicals and to add magnetic properties to siloles and germoles, thus creating a truly multifunctional material ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 12063 ff. (DOI: 10.1002/chem.202101415 ).